Determinant Indicators of Turnover Intentions, Work Productivity, Work Safety, Health and Human Relations - Ida Ayu Iswari Pidada (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACT This research aimed to Analyze indicators (1) safety affect the work productivity of employees at Melia Bali hotel Nusa Dua?, (2) health affect employee work productivity at Melia Bali hotel Nusa Dua?, (3) human relations influence employee work productivity at Melia Bali hotel Nusa Dua?,(4) safety affect employee turnover intentions at the Melia Bali hotel Nusa Dua?, (5) health affect employee turnover intentions at Melia Bali hotel Nusa Dua?, (6) work productivity affect employee turnover intentions at Melia Bali hotel?. Which all the reasons of this research is aimed to Analyze indicators that determine turnover intentions. This research used quantitative method. The subject in this study involved 115 employees. The Collecting data method used observation and questionnaire. The sampling method in this study using a type of non-probability sampling with combination method: purposive sampling-accidental sampling-quota sampling.  The collected data analyzed with SEM analysis of AMOS version 20.0.The results showed that there is a highly significant influence of Safety, Health, Human Relation, and Employees productivity towards Turnover intentions employees. In addition, based on the simple regression analysis model that indicated a positive and significant influence of Safety, Human Relation, toward Employees productivity. Then, there is a positive and highly significant influence between Employees productivity towards Turnover intentions.